Identification of potential maturity indicators for harvesting cacao (2020)
Cocoa production is a complex process where the conditions of the raw materials decisively impact the final quality of the product. Three universal clones (CCN51, ICS95, and TSH565) from the Department of Huila in Colombia were evaluated to characterize the ripening process of cocoa fruits. Maturity indicators were identified by following the evolution of basic fruit characteristics, including size, weight, seed count, depth and distance between grooves, width and length of the apex, diameter and length of the seed, moisture content, color parameters, fruit firmness, soluble solids content, pH, and acidity. The results indicated that each cocoa clone has a unique set of ripeness parameters: color for ICS95; firmness and weight of the seed for CCN51; and color, morphological characteristics of the apex and grooves, weight, moisture content, pH, and total soluble solids for TSH565. The establishment of reliable, practical, and objective ripeness indicators for each cocoa clone will allow more homogenous cocoa pods to be selected for fermentation, which will ultimately contribute to improved quality and homogeneity of cocoa and its derived products.